Respiratory flows as a method for safely preventing the coronavirus transmission (Covid-19) - Córdova, A.; Latasa, I. (Apunts Medicina de l'Esport, 2020)
The spread of CoV-2 occurs mainly by respiratory droplets. Its dispersion depends on several factors: viscoelasticity of fluid, ventilation, evaporation rate, exhalations, sneeze or cough. At moment, the preventive distance to avoid the contamination has been established in 1-2 m. We believe that it is necessary to review this aspect, because the respiratory flows change with the intensity of physical activity.The ventilatory response can be evaluated in terms of ventilatory demand or ventilatory efficiency. During maximal effort tests, athletes mobilize an extraordinary amount of air arriving to 150/200 L/min. The respiratory volume follows increase in linear progression during the test in function of power developed. When the air volume is increased 10 times, we think that the distance should be around 6-7 m.